Penyelesaian Sengketa Pertanahan Melalui Perbaikan Kualitas Data Pertanahan Di Kabupaten Manggarai Barat - Lusiana Maryati Karuni Poso Teku; Mujiati Mujiati; Dian Aries Mujiburohman (PERSPEKTIF, 2022)
One of the causes of land problems is the absence of complete and accurate data on registered land ownership. This happens because the digitization process has not yet been completed, whether the certificates, land books or letters of measurement and maps. So, the purpose of this study is to analyze the quality of land data to identify and resolve land disputes. The method used is a qualitative descriptive method, with the results showing that one of the Independent Land Data Quality Improvement activities (PKDPM) produces a dispute map containing the names of the parties with problems and the location of the land indicated as problematic. Based on the dispute map, it can identify 58 (fifty-eight) land disputes which are classified into 4 (four) namely overlapping, boundary disputes, inheritance disputes and land ownership disputes. However, out of 58 disputes, only 5 cases could be resolved through mediation at the West Manggarai Land Office. So, it can be concluded that PKDPM activities are only able to identify disputes, but are not able to resolve existing disputes.